A network-wide exact optimization approach for multiobjective routing with path protection in multiservice multiprotocol label switching networks. Issue 7 (3rd July 2017) - Girão-Silva, Rita; Craveirinha, José; Gomes, Teresa; Martins, Lúcia; Clímaco, João; Campos, João
ABSTRACT: A multiobjective routing model for multiprotocol label switching networks with multiple service types and path protection is presented in this article. The routing problem is formulated as a biobjective integer program, where the considered objectives are formulated according to a network-wide optimization approach, i.e. the objective functions of the route optimization problem depend explicitly on all traffic flows in the network. A disjoint path pair is considered for each traffic trunk, which guarantees protection to the associated connection. A link-path formulation is proposed for the problem, in which a set of possible pairs of paths is devised in advance for each traffic trunk. An exact method (based on the classical constraint method for solving multiobjective problems) is developed for solving the formulated problem. An extensive experimental study, with results on network performance measures in various randomly generated networks, is also presented and discussed.